MINIMASI BIAYA DISTRIBUSI KACANG KEDELAI MENGGUNAKAN METODE CLARKE & WRIGHT SAVINGS HEURISTIC DI UD. HASIL BUMI - KHADIJAH, AFNI; Saepul (Prodi Teknik Industri, Fakultas Teknik, 2025)
This study discusses determining the distribution route of soybeans in UD. Hasil Bumi use yhe Clarke and wright saving heuristic algorithm, to determine the proposed shortest route according to the vehicle and its capacity to reduce product delivery costs which are more profitable for the company. Comparison of the results of the soyben delivery route in UD. The current yield of the earth is 363 KM at a cost of Rp. 798,782 and a total request of 7020 KG while using the Clarke and wright saving heuristic algorithm, the total discance traveled is 329.3 KM at a cost of Rp. 780,249 and a total demand of 7020 KG, this algorithm is able to provide a mileage saving of 33.7 or 9.28% and a cost of Rp. 18,782. This can show thath the clatke and wright saving heuristic method is able to minimize the distribution distance of soybeans in Ud. corp.